Analysis of the factors influencing on bird nesting and its impact on railway operation. Issue 1 (28th July 2020) - Shi, Lijuan; Jia, Zuoning; Sun, Huize; Tian, Mingshu; Chen, Liquan
Abstract : Purpose: This paper aims to study the affecting factors on bird nesting on electronic railway catenary lines and the impact of bird nesting events on railway operation. Design/methodology/approach: First, with one year's bird nest events in the form of unstructured natural language collected from Shanghai Railway Bureau, the records were structured with the help of python software tool. Second, the method of root cause analysis (RCA) was used to identify all the possible influencing factors which are inclined to affect the probability of bird nesting. Third, the possible factors then were classified into two categories to meet subsequent analysis separately, category one was outside factors (i.e. geographic conditions related factors), the other was inside factors (i.e. railway related factors). Findings: It was observed that factors of city population, geographic position affect nesting observably. Then it was demonstrated that both location and nesting on equipment part have no correlation with delay, while railway type had a significant but low correlation with delay. Originality/value: This paper discloses the principle of impacts of nest events on railway operation.